Association between Allergic diseases and irritable bowel syndrome (IBS) - Kazem Pourabbas; Maryam Baghiani; Abbas Khalili (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Irritable Bowel Syndrome (IBS) is a functional gastrointestinal disease and the most common cause of long-term abdominal pain and bowel disorders. The association between allergic disease and IBS is limitedly understood. we aimed to investigate the frequencies of asthma, eczema and allergic rhinitis in IBS patients and as well as the relationship of these allergic diseases with IBS.Materials and Methods: In this case-control study, we included 300 patients with IBS over 5 years of age who were referred gastrointestinal clinics of Shahid Sadoughi University of Medical Sciences, Yazd in 2021. The control group includes 300 healthy individuals without IBS. Demographic and clinical information of two groups were recorded in the International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire, based on which eczema, asthma and allergic rhinitis were diagnosed. Then, the frequencies of asthma, allergic rhinitis and eczema was then compared between the two groups.Results: The frequency of asthma was significantly higher in the IBS group (P